48‐2: Flipping‐free Light Field Mirage Using Multiple Light Field Displays. Issue 1 (28th June 2021) - Momonoi, Yoshiharu; Yamamoto, Koya; Yokote, Yoshihiro; Sato, Atsushi; Takaki, Yasuhiro
Abstract : We have previously proposed the light field mirage which replaced the parabolic mirrors in Mirage with multiple flat‐panel light field displays. We propose two techniques to eliminate rays generating the flipping. The lower half display system was constructed to verify the proposed techniques.